2019
DOI: 10.1136/neurintsurg-2018-014637
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich clots as identified by Martius Scarlet Blue staining are isodense on NCCT

Abstract: BackgroundCurrent studies on clot characterization in acute ischemic stroke focus on fibrin and red blood cell composition. Few studies have examined platelet composition in acute ischemic stroke clots. We characterize clot composition using the Martius Scarlet Blue stain and assess associations between platelet density and CT density.Materials and methodHistopathological analysis of the clots collected as part of the multi-institutional STRIP registry was performed using Martius Scarlet Blue stain and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 20 publications
1
71
0
Order By: Relevance
“…In a previous study we demonstrated that platelet-rich clots, as identified using the MSB stain, are isodense on NCCT [20]. In that study, we quantified red blood cells, white blood cells, Fibrin and Platelets/Other.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study we demonstrated that platelet-rich clots, as identified using the MSB stain, are isodense on NCCT [20]. In that study, we quantified red blood cells, white blood cells, Fibrin and Platelets/Other.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, although other factors are involved in the achievement of a favorable clinical outcome, such as good collaterals5 and shorter time to reperfusion (TTR),6 an adequate recanalization grade remains an independent predictor of functional independence7–9 although futile recanalizations are still observed. Some authors have proposed different predictors of recanalization according to the clot imaging characteristics, such as the susceptibility vessel sign on MRI10 and attenuation on CT scan,11 as well as the thrombus length12 and the clot burden score 13. In this paper we aim to assess the recanalization rate obtained with SR or CA according to the phenotype of the occlusion site, defined as ‘regular’ and ‘irregular’ (see online supplemental figure 1) in a cohort of patients with a M1-middle cerebral artery (M1-MCA) occlusion included in the ASTER trial.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6,19] A recent study has demonstrated that platelet-rich thrombi identi ed by MSB staining are isodense on NCCT. [10] We found that 'white' thrombi are smaller and less hyperdense compared to the other clots.…”
Section: Discussionmentioning
confidence: 58%
“…We used the MSB stain which allows for a signi cantly better differentiation of the major components of clots than the traditional hematoxylin & eosin stain. [10] 'White' clots were platelet-rich compared to 'red' thrombi. We con rmed the presence of calci cation in one case using von Kossa stain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation